Perceptions of the International Baccalaureate (IB) in Canadian Universities - Fitzgerald, Saira (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2017)
This article presents the results of the first Canada-wide survey on how university admissions personnel view the International Baccalaureate Diploma Program (IBDP) in relation to other curricula. The purpose of this study was twofold: (i) to move beyond anecdote and discover how Canada compares with universities in the UK and Australia/NZ, and (ii) to determine whether a dominant or hegemonic discourse surrounding the IBDP exists. Building on a small-scale pilot of perceptions in Ontario universities, the present study replicates two International Baccalaureate Organization studies (in the UK, 2003, and in Australia/NZ, in 2007) in the Canadian context. Results reveal a pattern of responses consistent with the previous studies—i.e., a confident positive general view, combined with uncertainty regarding specific aspects of the IBDP. Such widespread and consistent views suggest the existence of a dominant or hegemonic discourse surrounding the IBDP, constructing it as the standard of excellence in pre-tertiary education, which has important implications for publicly funded education in Canada.